Effect of Herbs and Herbal Products Feed Supplements on Growth in Fishes: A Review - Shakya, Shubha Ratna (Nepal Journal of Biotechnology, 2017)
The herbs and herbal products added to the feed cure many diseases, promote growth, reduce stress, improve immunity and prevent infections in fish under culture. The addition of herbs and herbal products in fish diet is cheaper and environmental friendly with low side effect to the fish and consumers. Hence, their use as drugs in disease management in aquaculture is gaining popular. They are better than various antibiotics and vaccines used in the treatment of diseases. The present review highlights the importance of herbs and herbal products supplementation in fish feed for better fish production. Nepal Journal of Biotechnology. Dec. 2017 Vol. 5, No. 1: 58-63